Influence of nicotine on the adherence of Candida albicans ATCC 14053 and Candida parapsilosis ATCC 22019 and expression of selected binding-related genes - Gunasegar, S. (Taylor & Francis, 2017)
Smoking is considered one of the main factors for development of dental plaque. Yeasts have been described to contribute to the plaque community. The aim of this study was to investigate the influence of nicotine on the growth of planktonic cells and biofilm, cell aggregation, surface hydrophobicity, cell adherence and binding-related genes expressed by Candida albicans and Candida parapsilosis in vitro. The relative number of viable fungal cells was determined based on viable plate counts. The biofilm growth was quantified using the crystal violet assay. Reverse transcription-polymerase chain reaction was used to evaluate the regulation of selected genes associated with adherence. The results indicated that nicotine enhanced the growth of both planktonic and biofilm oral fungal cells. Cell surface hydrophobicity and the expression of Hyphal Wall Protein 1 (HWP1) and agglutinin-like sequences 3 (ALS3) of C. albicans and C. parapsilosis were found to increase relative to the nicotine concentrations. The results suggest that nicotine can enhance the growth of C. albicans and C. parapsilosis in vitro and influence their adherence to the surface of microplate wells that mimic as the tooth surface.